Factors Influencing the Risk Averse Consumer Base Towards Online Shopping: A Perspective on Evolving Shopping Behaviour in Malaysia - Jafary, Khadija Hasan (2016)
Purpose: This study aims to investigate whether online environment cues influence consumer online purchase intention and whether this impact is mediated by consumer trust and shopping enjoyment. The study also explores the direct influence and relevance of each environment cue on influencing purchase intention. Design/methodology/approach: The study proposed a research framework for testing the relationships among the constructs based on the stimulus-organism-response framework. After the validation of measurement scales, empirical analyses were performed using various statistical tools. Findings – The findings of this research confirm that website quality and website brand affect consumers’ trust, and in turn, consumer purchase intention. Notably, this study finds that the shopping enjoyment not only mediates the relationship between website quality and purchase intention but also it is the strongest predictor for online purchase intention. Furthermore, return policy has been found to positively influence purchase intentions and risk perceptions of consumers negatively related to purchase intention. Practical Implications: Online retailers should focus their marketing strategies more towards establishing an enjoyable website design as it has a stronger influence in gaining consumer trust than website brand. Additionally, lenient return policies should complement a good and reputable website design. Originality /Value: This study proposed a model for empirically analysing the links between web site quality, web site brand, trust, perceived risk, shopping enjoyment and purchase intention towards the online retailer. The empirical evidence of this study will contribute to the literature in online shopping purchase intention